Ménage-à-Trois: The Ratio of Bicarbonate to CO2 and the pH Regulate the Capacity of Neutrophils to Form NETs - Maueröder, Christian; Mahajan, Aparna; Paulus, Susanne; Gößwein, Stefanie; Hahn, Jonas; Kienhöfer, Deborah; Biermann, Mona H.; Tripal, Philipp; Friedrich, Ralf P.; Munoz, Luis E.; Neurath, Markus F.; Becker, Christoph; et al. (Frontiers in Immunology, 2016)
In this study we identified and characterized the potential of a high ratio of bicarbonate to CO2 and a moderately alkaline pH to render neutrophils prone to undergo neutrophil extracellular trap (NET) formation. Both experimental settings increased the rate of spontaneous NET release and potentiated the NET-inducing capacity of phorbol esters (PMA), ionomycin, monosodium urate and LPS. In contrast, an acidic environment impaired neutrophil extracellular trap formation both spontaneous and induced. Our findings indicate that intracellular alkalinization of neutrophils in response to an alkaline environment leads to an increase of intracellular calcium and neutrophil activation. We further found that the anion channel blocker DIDS strongly reduced NET formation induced by bicarbonate. This finding suggests that the effects observed are due to a molecular program that renders neutrophils susceptible to neutrophil extracellular trap formation. Inflammatory foci are characterized by an acidic environment. Our data indicates that NET formation is favored by the higher pH at the border regions of inflamed areas. Moreover our findings highlight the necessity for strict pH control during assays of neutrophil extracellular trap formation.